Significant usage of slab and wall from technique in industrialised building system (IBS) for low cost high - rise apartments construction [compact disc] - 414826 Redzuan Ab. Rahman (Skudai : Universiti Teknologi Malaysia, 2006)
Thesis (Sarjana Sains (Pengurusan Pembinaan)) - Universiti Teknologi Malaysia, 2006